Evaluasi Program Penerimaan Peserta Didik Baru (PPDB) Pada Sistem Zonasi Menggunakan Model CIPP di Kabupaten Trenggalek - Diki Darmawan; Shevia Dwi Diantari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to evaluate the New Learner Admission Program (PPDB) in Trenggalek Regency, especially the zoning system, using the CIPP (Context, Input, Process, and Product) model. The research method used is qualitative research with the research subject as the Head of the Subdivision of Program Planning and Evaluation of the Education, Youth and Sports Office of Trenggalek Regency. Data were analyzed descriptively analytically through interviews and PPDB implementation reports. The evaluation results show that the context of PPDB in Trenggalek Regency includes the determination of zoning areas, the percentage of capacity, and the issuance of technical guidelines. The input evaluation includes the online PPDB application and socialization to stakeholders. The PPDB process involves announcement, registration, selection, and announcement of the determination of students. Meanwhile, product evaluation includes the re-registration process, integration of PPDB data in Dapodik, and reporting on the implementation of PPDB. Comprehensively, the evaluation using the CIPP model provides a comprehensive picture of the effectiveness, efficiency, and fairness of the zoning system implementation in PPDB. The evaluation findings can be used to improve transparency, efficiency, and fairness in the zoning PPDB system in Trenggalek.